Islam in a globalized world: the challenges of human right, law, and interfaith harmony - Mohamad Atho Mudzhar (The Center for Research and Development of Religious Life, the Office of Research of Development, and Training, Ministry of Religious Affairs, Republic of Indonesia, 2011)
st,3/nr,c.1-3